2009
DOI: 10.1146/annurev-nutr-080508-141056
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Protein, Weight Loss, and Weight Maintenance

Abstract: The role of dietary protein in weight loss and weight maintenance encompasses influences on crucial targets for body weight regulation, namely satiety, thermogenesis, energy efficiency, and body composition. Protein-induced satiety may be mainly due to oxidation of amino acids fed in excess, especially in diets with "incomplete" proteins. Protein-induced energy expenditure may be due to protein and urea synthesis and to gluconeogenesis; "complete" proteins having all essential amino acids show larger increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
412
4
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(447 citation statements)
references
References 106 publications
19
412
4
12
Order By: Relevance
“…Intakes of carbohydrate, protein or fat were not considered because those macronutrients contribute to the dietary insulin index and insulin load. However, as protein may also conduce higher lean mass, 39 we included this macronutrient as a covariate in a further step (data not shown) and observed a similar association between higher dietary insulin index and insulin load during puberty, and higher %BF in young adulthood (insulin index: P for trend ¼ 0.0965; insulin load: P for trend ¼ 0.07).…”
Section: Dietary Insulin Index and Body Composition G Joslowski Et Almentioning
confidence: 93%
See 1 more Smart Citation
“…Intakes of carbohydrate, protein or fat were not considered because those macronutrients contribute to the dietary insulin index and insulin load. However, as protein may also conduce higher lean mass, 39 we included this macronutrient as a covariate in a further step (data not shown) and observed a similar association between higher dietary insulin index and insulin load during puberty, and higher %BF in young adulthood (insulin index: P for trend ¼ 0.0965; insulin load: P for trend ¼ 0.07).…”
Section: Dietary Insulin Index and Body Composition G Joslowski Et Almentioning
confidence: 93%
“…In addition, further adjustment for protein enhanced the association between dietary insulin demand and body fat. This may reflect a bi-directional relevance of dietary protein, which may contribute to a higher lean body mass on the one hand 39 and a higher insulin secretion 17 or lower insulin clearance on the other hand. 48 The relationship between a higher dietary insulin demand during puberty and a higher %BF in young adulthood was attenuated by the additional consideration of baseline %BF.…”
Section: 9mentioning
confidence: 99%
“…Satiety was greater in the protein group than the habitual energy group (67) . Increased satiety has been shown to result from acute protein consumption and high-protein diets (69)(70)(71)(72) . Satiety measured in the postabsorptive state may be attributed to increased resting energy expenditure (68)(69)(70) .…”
Section: Hypoenergetic Weight Lossmentioning
confidence: 99%
“…2,3 A comprehensive review from 2009, studying the epidemiological evidence on the associations between diet (both at macronutrient level and food level) and subsequent weight gain and obesity, however, concluded that based on the selected literature 'Levels of protein intake, regardless of source, are not associated with subsequent excess weight gain or obesity although the results were inconsistent'. 4 Among the eight cohort studies found on adults, six studies did not find any significant associations between total protein intake and subsequent changes in weight or waist circumference (WC).…”
Section: Introductionmentioning
confidence: 99%